2021
DOI: 10.1016/j.biopsych.2020.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Patterns of Brain-Behavior-Environment Associations in the Adolescent Brain and Cognitive Development Study

Abstract: BACKGROUND: Adolescence is a critical developmental stage. A key challenge is to characterize how variation in adolescent brain organization relates to psychosocial and environmental influences. METHODS: We used canonical correlation analysis to discover distinct patterns of covariation between measures of brain organization (brain morphometry, intracortical myelination, white matter integrity, and resting-state functional connectivity) and individual, psychosocial, and environmental factors in a nationally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 53 publications
7
37
0
1
Order By: Relevance
“…Although studies using the ABCD sample have begun uncovering associations between aspects of children’s environments and rsFC ( Thijssen et al, 2020 , Modabbernia et al, 2021 , Ellwood-Lowe et al, 2020 , Hong et al, 2021 , Rakesh et al, 2021b ), approaches that aim to disentangle the effects of broader socioeconomic context (e.g., SES, parental education) from youths’ downstream experiences of these broader contexts (e.g., their home environment) remain to be explored. Based on prior work mentioned above (e.g., Brody et al, 2019 ), it is likely that the magnitude of SES effects on brain connectivity will be stronger in the context of proximal environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies using the ABCD sample have begun uncovering associations between aspects of children’s environments and rsFC ( Thijssen et al, 2020 , Modabbernia et al, 2021 , Ellwood-Lowe et al, 2020 , Hong et al, 2021 , Rakesh et al, 2021b ), approaches that aim to disentangle the effects of broader socioeconomic context (e.g., SES, parental education) from youths’ downstream experiences of these broader contexts (e.g., their home environment) remain to be explored. Based on prior work mentioned above (e.g., Brody et al, 2019 ), it is likely that the magnitude of SES effects on brain connectivity will be stronger in the context of proximal environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…These findings raise the possibility that the P factor involves alterations in networks involved in the generation of spontaneous thought (default mode network, DMN) and bottomup attention (ventral attention network, VAN), as well as networks involved in cognitive control (e.g., frontoparietal network, FPN, dorsal attention network, DAN; cingulo-opercular network, CO) [14]. Recent studies found altered functional-connectivity patterns associated with transdiagnostic dimensions [15][16][17][18][19][20][21], but findings have been mixed and await further clarification.…”
Section: Introductionmentioning
confidence: 99%
“…Nörogörüntülemeyle yapılan bir çalışmada sosyoekonomik koşullar, ebeveyn ilgisi, perinatal olaylar ve bilişsel yetenek düzeyi psikopatoloji yüküyle en tutarlı şekilde ilişkilendirilen faktörler olarak saptanmıştır (68). Çalışmamızın bulguları arasında bu faktörlerden perinatal olaylar dışındaki üçü doğrudan veya dolaylı olarak bulunmaktadır.…”
Section: Discussionunclassified